Does aid induce foreign direct investment: Updated evidence from a quasi-experiment - Tian, Junyan (Oxford University Press, 2025)
While the catalytic effect of aid on foreign direct investment (FDI) has long been an implicit consensus among many policymakers and practitioners, assessments of this causal relationship remain limited and are not always reliable. To mitigate this evidence gap, this study applies an instrumental variable approach that leverages the graduation of the International Development Association (IDA) income threshold as a quasi-experiment to identify the causal linkage between foreign aid and FDI. The analysis reveals that a 1 percent drop in the ratio of aid to gross national income leads to a decline in FDI relative to gross domestic product by 0.9 percent in 42 developing countries from 1987 to 2019. In face of the aid shock induced by IDA graduation, governments in recipient countries restrict their financial policy openness, through which aid could significantly impact subsequent foreign private investment. Results emphasize the necessity of concerted policy interventions to mitigate this negative aid shock.